Analisis Kualitas Mikrobiologi Air Pada Daerah Terdampak Bencana Di Desa Rogo Kecamatan Dolo Selatan Kabupaten Sigi - Hasanah, Hasanah (Preventif : Jurnal Kesehatan Masyarakat, 2022)
Flash floods cause environmental damage problems that can be affect the quality clean of water and can be trigger outbreaks of infectious diseases, one of which is diarrhea that occurs after the flood. The purpose of this study was to analyze the microbiological quality of water in clean and drinking water sources in Rogo Village, South Dolo District, Sigi Regency which was carried out in July-August 2022. This type of research was observational through a descriptive approach with laboratory tests to determine the presence of total bacteria. Coliform and Escherichia coli in clean water and drinking water samples. The data were analyzed using descriptive analysis techniques and presented in the form of tables and narratives. The results of the analysis showed that in the examination of clean water samples for the category of well water and river water, the presence of Total Coliform was found but it was still below the standard so that it had not passed the quality standard. For drinking water, the gallon water category was found to have Total Coliform, while in boiled water it was not detected. The quality of clean water and drinking water in Rogo Village has met the requirements and is suitable for consumption.